A study of dynamic network selection in wireless overlay network - Mohd Zaini, Khuzairi; Mohd Shariff, Azizul Rahman; Osman, Baharuddin (2015)
WLAN has been considered as a compliment technology for cellular network in the heterogeneous wireless network. Thus, seamless connection between these technologies play important role as the performance indicator. In this paper, we consider the user's velocity and channel holding time to predict the user's dwelling time in the WLAN area to assist in the initial network selection. If the expected completion time is lower than the predictive travelling time within the coverage area, together with the load and service characteristics, the algorithm will select WLAN instead of cellular network. Based on the discrete-event simulation, the results show that the proposed solution has better performance as compared to the location-based (WLAN First) and mobility threshold proposals.